Frequency of inappropriate endotracheal tube cuff pressure and its variability in patients undergoing prolonged surgery: A prospective observational study: Endotracheal tube cuff pressure variation under general anaesthesia - Rehman Shamsi, Muhammad Fahad; Siddiqui, Ali Sarfraz (Journal of Ayub Medical College Abbottabad, 2023)
Background: Endotracheal tube (ETT) is inserted into the trachea to maintain the airway patency. Maintaining adequate ETT cuff pressure is important to ensure a proper seal to lower the risk of aspiration and tracheal trauma. This study was designed to assess the frequency of inappropriate ETT cuff pressure at the time of intubation and variation in ETT pressure at the end of a prolonged surgery. Methods: This study was conducted in the Department of Anaesthesiology, Aga Khan University from October 2019 to March 2020. All adult patients of both genders, undergoing prolonged surgery under general anaesthesia were included. Patients were intubated with an appropriate size ETT, and the cuff was inflated with air. ETT cuff pressure was measured after intubation and, if inappropriate, was adjusted to an appropriate level. ETT cuff pressure reading was noted at the end of prolonged surgery to assess any variation. Results: Fifty-eight patients were included, 64% were females. The mean age was 47.36 years. The frequency of inappropriate ETT cuff pressure at the time of intubation was 60.3% which was corrected before the start of surgery. At the end of surgery, 70.7% of patients showed variations in ETT cuff pressures with majority (33%) having a variation of 51 to 70 (81-100 cm H2O). Conclusions: The frequency of inappropriate endotracheal tube cuff pressure at the time of intubation was found to be 60.3%. In 70.7% of patients, ETT cuff pressure at the end of prolonged surgery was inappropriate.